Hubungan Antara Literasi Digital dengan Kemampuan Berpikir Kritis Generasi Z - Nurul Pauziah; Tia Muthiah (UNISBA Press, 2023)
Abstract. Currently, the advancement of information technology is so rapid which has implications for the ease of humans in interacting and transacting. The convenience obtained for human life is to launch daily activities / activities, such as work, school, and college. Through various information technology devices, humans can obtain all kinds of information that can be accessed easily and cheaply through social media networking sites. The most popular social media networking site by the public is YouTube, where Indonesian people are ranked 3rd YouTube users in the world. This study is entitled